Can cryogenic freezing preserve the quality of fruit matrices during long-term storage compared to the mechanical method? - Piyush Kumar Jha; Nicolas Chapleau; Pierre-Emmanuel Meyers; Didier Pathier; Alain Le-Bail (Applied Food Research, 2024)
This study compares cryogenic freezing (–80 °C and 0.5 m/s air velocity) and mechanical freezing (–40 °C and 4 m/s air velocity) conditions/methods on the quality of melon and apple tissues during a 90-day storage. Samples were analysed on the 7th, 30th, 60th, and 90th day for various qualities: pH, TSS, titratable acidity, total quality index, enzymology, vitamin C, firmness, colour, exudate, soluble protein, and microstructure. Results show pH, °Brix, titratable acidity, and total quality index changes after freezing. Trends differed between melon and apple. Melon pH increased after freezing, while apple pH decreased. Titratable acidity decreased post-freezing for both. °Brix in melon initially decreased but increased in apples with longer storage. Freezing conditions and storage durations affected total quality index. Melon firmness increased, while apple firmness decreased compared to fresh samples post-freezing. Freezing condition did not affect firmness, but storage duration impacted it. Colour was influenced by both freezing treatment and methods, as well as the duration of frozen storage for melons. The L* value decreased for both matrices following freezing treatment. The a* and b* values of apples increased after post-freezing treatment compared to fresh. The a* value of fresh and cryogenically frozen melons was similar. Colour differences were more pronounced for mechanically frozen samples, increasing during storage for apples, while a fluctuating trend was observed for melons. Apple samples exhibited a reduction in polyphenol oxidase (PPO) activity post-freezing, while peroxidase activity (POD) displayed some increase in melons. PPO activity was lower for cryogenic freezing, decreasing with storage, while POD activity was storage-duration impacted. Exudation was lower in cryogenic freezing for both matrices. Soluble protein content was higher in cryogenic frozen samples, though fluctuating. Cryogenic freezing slightly reduced pore sizes in apples, preserving microstructure better, unlike mechanical freezing which damaged cellular structure.